Gender Issues in Biogas Promotion and Use in Kenya: A preliminary review - Wilkes, Andreas; Dijk, Suzanne van (2017)
This review has been undertaken in the context of preparation of a concept note for the Kenya dairy NAMA. Biogas promotion is one of the project components. Mitigation actions should aim to achieve greater, more effective, sustainable, and equitable climate change results, outcomes and impacts; ensure that women and men have equal opportunity to contribute to, and benefit from supported activities; and mitigate against potential project risks for women and men arising from the supported activities.